Computer-automated process planning for world-class manufacturing - Nolen, James (Manufacturing engineering and materials processing, 1989)
Presents an information on computer-aided manufacturing from selection and installation to operation in a world-class manufacturing environment. This title includes a wide range of process planning applications. It shows how to use computer-automated process planning data.